Ireland : First Post-Program Monitoring Discussions. (IMF Staff Country Reports; Country Report ;, 2014)
This paper focuses on Ireland's First Post-Program Monitoring Discussions. The Irish economy is beginning its recovery from crisis but determined efforts remain vital to sustain strong growth while reducing vulnerabilities. Following a smooth exit from the EU-IMF supported program, strong job creation and other indicators suggest economic recovery is broadening. Together with other European periphery countries, Ireland currently enjoys favorable financial market conditions, and the government has resumed bond auctions at historically low yields. Unemployment is still high even after a significant decline in recent years, and public and private debt burdens remain a source of risk to the strength and durability of the recovery.